Alcohol's Modulation of Basolateral Amygdala Oscillations - DiLeo, Alyssa. (Tufts University. Tisch Library., 2022)
Thesis (Ph.D.)--Tufts University, 2022.; Submitted to the Dept. of Neuroscience.; Advisor: Jamie Maguire.; Committee: Leon Reijmers, Steve Moss, Klaus Miczek, Paul Davies, and Dong Kong.; Keyword: Neurosciences.